Optimalisasi Kinerja Panitia Mahasiswa melalui Pelatihan Pengelolaan Lomba Poster Ilmiah, Essay Ilmiah, dan Video Edukasi pada Kegiatan POSIL 2026 di Institut Kesehatan Deli Husada Deli Tua: Pelatihan Pengelolaan Lomba - Tasnim Tasnim; Herri Novita Br Tarigan; Putri Ayu Yessy Ariescha; Sofia Rahmi; Hariati Hariati; Alfi Syahri (Jurnal Pengabdian Masyarakat Putri Hijau, 2026)
The 2026 Sports, Arts and Science Week (POSIL) at the Deli Husada Deli Tua Health Institute is an annual event aimed at improving students' academic abilities, creativity, and organizational skills. One of the POSIL 2026 activities is the Scientific Poster, Scientific Essay, and Educational Video competitions involving students as the organizing committee. This community service (PKM) activity aims to optimize the performance of the student committee through training and mentoring in managing scientific competition activities. The coaching activity was carried out on May 4–16, 2026 at the Deli Husada Deli Tua Health Institute Campus, Deli Serdang Regency, North Sumatra Province, involving 7 student committee members. The methods used included direct direction, assignments, supervision, and mentoring from the preparation stage to the announcement of the competition winners. The mentoring activities included preparing promotional flyers, developing registration procedures, preparing an online registration system, uploading works and assessing them using Google Forms, coordinating and appointing a jury team, and mentoring the assessment process and determining the competition winners. The results of the activity demonstrated that the student committee was able to carry out all stages of the activity according to established procedures. The committee also demonstrated improved organizational, coordination, communication, and administrative management skills in scientific activities. Furthermore, the competition was successfully implemented and produced winners in the Scientific Poster, Scientific Essay, and Educational Video categories. This activity can serve as a model for student development in improving managerial and leadership skills through professional and sustainable management of campus scientific activities.